2007
DOI: 10.4269/ajtmh.2007.76.698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brucellosis by PCR and Persistence After Treatment in Patients Returning to the Hospital for Follow-Up

Abstract: Polymerase chain reaction (PCR) was applied to confirm the diagnosis of brucellosis and to study its clearance in response to the standard treatment regimen with doxycycline and rifampin at hospitals in Callao and Lima, Peru. The PCR confirmed the diagnosis in 23 (91.7%) patients with brucellosis including 12 culture-confirmed cases. For patients treated at the hospital in Callao, PCR was positive for all samples collected during and at the conclusion of treatment and for 76.9% of follow-up samples collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…Earlier PCR studies indicated that the pathogen may persist in the blood of patients during and after the end of treatment with the standard combination therapies consisting of doxycycline with rifampicin and doxycycline with streptomycin, which have been recommended by the WHO [12][13]25]. In our study, we found that the pathogen persisted more than three months in patients treated with doxycyline and ciprofloxacine.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Earlier PCR studies indicated that the pathogen may persist in the blood of patients during and after the end of treatment with the standard combination therapies consisting of doxycycline with rifampicin and doxycycline with streptomycin, which have been recommended by the WHO [12][13]25]. In our study, we found that the pathogen persisted more than three months in patients treated with doxycyline and ciprofloxacine.…”
Section: Discussionsupporting
confidence: 62%
“…However, therapeutic failure and the development of persistent diseases as well as the high relapse rate are of concern. Earlier studies using PCR have indicated that the pathogen may persist in the blood of the patient during and following treatment providing a plausible explanation for the suboptimal effect of current treatment regimens [12][13][14]. Other treatment regimens including treatment with doxycycline and ciprofloxacin have not been demonstrated to be more effective than the WHO recommended regimens [15].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been made on the development of molecular diagnostic assays based on amplification of different genomic targets by the polymerase chain reaction (PCR) for the diagnosis of human brucellosis. A recent publication 5 has indicated the persistence of DNA in the serum, even after completion of standard treatment regimen, ranging from weeks to months, thus failing to establish these molecular assays as routine diagnostic methods as yet. Hence, the laboratory diagnosis is often serologically directed to detection of Brucella -specific antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…However, our group and others have demonstrated the persistence of Brucella sp. DNA for long periods of time after the conclusion of therapy in asymptomatic patients (10,15,24). The practical role of quantitative real-time PCR (Q-PCR) in the laboratory diagnosis of chronic brucellosis and the assessment of clinical manifestations remains to be demonstrated.…”
mentioning
confidence: 99%